Mathematical Modeling and Kinetics of Removing Metal Ions from Industrial Wastewater - Jawad, Nizar; M. Naife , Tariq (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
The study's objective is to produce Nano Graphene Oxide (GO) before using it for batch adsorption to remove heavy metals (Cadmium Cd+2, Nickel Ni+2, and Vanadium V+5) ions from industrial wastewater. The temperature effect (20-50) °C and initial concentration effect (100-800) mg L-1 on the adsorption process were studied. A simulation aqueous solution of the ions was used to identify the adsorption isotherms, and after the experimental data was collected, the sorption process was studied kinetically and thermodynamically. The Langmuir, Freundlich, and Temkin isotherm models were used to fit the data. The results showed that Cd, Ni, and V ions on the GO adsorbing surface matched the Langmuir model with correlation coefficients (R2) of 0.999. Kinetic models studied showed that a pseudo-second-order model was followed and thermodynamically, the process was exothermic due to ∆H negative, the reduction in randomness because of negative ∆S. additionally, spontaneous adsorption of metal ions was ∆G negative values influenced.